1996
DOI: 10.1002/eji.1830260310
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage‐T cell interaction in murine salmonellosis: selective down‐regulation of ICAM‐1 and B7 molecules in infected macrophages and its probable role in cell‐mediated immunity

Abstract: Vaccine development and understanding of cellular immune modulatory mechanisms in salmonella infections have been impeded due to the paucity of data on antigens capable of eliciting effective immune responses. The present study was done to evaluate the efficacy of five major purified salmonella antigens (porins, pili, flagella, outer membrane proteins and heat shock proteins) in modulating T cell-macrophage interactions which play a central role in resistance to and recovery from infection with several intrace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…This work has shown that CD28-B7 interactions have a prominent role in governing the host immune response to parasitic and bacterial infections (10,24,27,40,41,43). The goal of the present work was to determine the specific role of T cells in intra-abdominal abscess formation.…”
Section: Discussionmentioning
confidence: 94%
“…This work has shown that CD28-B7 interactions have a prominent role in governing the host immune response to parasitic and bacterial infections (10,24,27,40,41,43). The goal of the present work was to determine the specific role of T cells in intra-abdominal abscess formation.…”
Section: Discussionmentioning
confidence: 94%
“…Macrophages have been shown to upregulate B7 molecules when exposed to Salmonella extracts in vitro (8), indicating that the activation of T-cell responses requiring CD28 costimulation may be enhanced by bacterial products. Indeed, lipopolysaccharide (LPS) is often used as an adjuvant for protein antigens due to its capacity to induce costimulatory molecules and the production of inflammatory cytokines by antigen-presenting cells (16,34,36).…”
Section: Discussionmentioning
confidence: 99%
“…Elution was performed by using a linear salt gradient (20 ml): 20 mM Tris (pH 7.5) to 20 mM Tris containing 1 M NaCl (pH 7.5). Fractions were dialysed and analysed on SDS-PAGE [5].…”
Section: Purification Of Porinsmentioning
confidence: 99%
“…In addition, an important co-stimulatory signal must be delivered from the antigen-presenting cell. In earlier studies, we reported that infection with live S. typhimurium in vitro causes a decreased expression of B7 and intracellular adhesion molecule-1 (ICAM-1) and that these changes contribute to the depressed CMI responses during Salmonella infection [5].…”
Section: Introductionmentioning
confidence: 99%